The Concept of Information and Communication Technology on Human Capital Development: Content Analysis Method Approach - Rusminingsih, Diah; Harnani, Sri; Damayanti, Lina (AIBPM Publisher, 2022)
Our aim is to investigate the concepts in previous research on human capital through Information Communication Technology (ICT). We use a collection of scientific articles from emeralds as well as books written by experts in the field of Information Communication Technology (ICT) and human resources. Three important components of human resources in Industry 4.0 are workforce architecture with new interactions, embracing future human resources, and topologies that generate competencies anticipated by human resources. This Information Communication Technology study will analyze the notion of information technology. AI is one of the most widely used information and communication technologies (ICT) in Industry 4.0. The artificial intelligence (AI) generated by ICT is essential in implementing current and future ICT projects. ICT professionals should also consider their work environment as a pleasant work environment that substantially affects performance and results. The advantages of information communication technology or ICT in communicating and interacting effectively. ICT is very important to fulfill all human needs. Communication science and the quality of human resources are closely related.